Technology Lock-In and Optimal Carbon Pricing - Jonathan T. Hawkins-Pierot; Katherine R. H. Wagner (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper studies the implications of energy prices today for energy efficiency and climate policy in the future. If adjustment costs mediate manufacturing plants' responses to increases in energy prices, incumbents may be limited in their ability to re-optimize energy-inefficient production technologies chosen based on past market conditions. Using U.S. Census microdata and quasi-experimental variation in energy prices, we first show that the initial electricity prices that manufacturing plants pay in their first year of operations are important determinants of long-run energy intensity. Plants that open when the prices of electricity and fossil fuel inputs into electricity are low consume more energy throughout their lifetime, regardless of current electricity prices. We then estimate that the productivity of energy inputs is persistently lower for plants that open when electricity is cheap, and these differences in relative input productivities can fully explain the effects of entry-year electricity prices on subsequent energy intensity. We discuss how this "technology lock-in" increases the emissions costs of delayed action on carbon policy.
Keywords: 330